2020
DOI: 10.21203/rs.2.17065/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Informal caregivers’ views on the quality of healthcare services provided to older patients aged 80 or more in the hospital and 30 days after discharge

Abstract: Background: In the European Union (EU), informal caregivers provide 60% of all care. Informal caregiving ranges from assistance with daily activities and provision of direct care to helping care recipients to navigate within complex healthcare and social services systems. While recent caregiver surveys document the impact of informal caregivers, systematic reviews show that they have unmet needs. Because of the political desire to reduce the length of hospital stays, older patients are discharged from the hosp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Our findings identified that FCs appreciated that the interventions place the onus on healthcare providers to initiate communication. That FCs recognized their need for information but did not know what questions to ask concurs with other studies [47][48][49]. In a systematic review of the literature of how healthcare consumers enact involvement in care, Murray concluded that many healthcare consumers are receptive to receiving information but do not have the capacity to actively seek out the information they need [41] which may be related to health literacy (i.e., the ability to retrieve, process, and use health information) [50].…”
Section: Discussionsupporting
confidence: 82%
“…Our findings identified that FCs appreciated that the interventions place the onus on healthcare providers to initiate communication. That FCs recognized their need for information but did not know what questions to ask concurs with other studies [47][48][49]. In a systematic review of the literature of how healthcare consumers enact involvement in care, Murray concluded that many healthcare consumers are receptive to receiving information but do not have the capacity to actively seek out the information they need [41] which may be related to health literacy (i.e., the ability to retrieve, process, and use health information) [50].…”
Section: Discussionsupporting
confidence: 82%
“…Since transitions from one care organization to another are common in the LYOL, this might explain the low degree of satisfaction. Other studies from the perspective of informal caregivers have also observed problems in discharge management and unorganized transitions [30]. Future surveys using the same instrument may observe improvements in discharge management.…”
Section: Discussionmentioning
confidence: 88%
“…Lilleheie et al. (2020) found that informal caregivers of vulnerable patients want healthcare providers to be more responsive to family needs and preferences by providing information and engaging them in the care processes. Future work to inform and educate caregiver/care recipient dyads about relevant weight management information (including how to find and nuances specific to SCI nutrition and physical activity needs) and the importance of communicating this information is warranted.…”
Section: Discussionmentioning
confidence: 99%